The Secret of Successful Leadership—The Critical Match Between the Characteristics of Leaders, the Attributes of Subordinates, and the Circumstances of the Situation - Muczyk, Jan P. (Journal of Comparative International Management)

(untitled) (Management Futures, 2020)
Seldom has so much been written on such an important topic that has produced so little agreement and so much controversy. It starts with “what is leadership and how does it differ from managership?” It continues with the development of competing big, mid-range, and small leadership theories (Muczyk & Adler, 2002). Most recently, scholars are preoccupied with attempting to develop a leadership theory or model by creating a critical match between leader characteristics, subordinate attributes, and the circumstances of the situation. More and more, the influence of national cultures in this global economic village is taken into consideration. This effort is also an attempt at creating such a match in a cultural context that is perceived to be useful by practitioners, is based on reason, and factors in important variables identified in the accepted leadership theories or models.